Вплив модифікаторів, легування міддю і нікелем на структуру, механічні і експлуатаційні властивості перлітного високоміцного чавуну - Бубликов, В.Б.; Бачинський, Ю.Д.; Нестерук, О.П.; Берчук, Д.М.; Ясинська, О.О.; Ясинський, О.О.; Овсянников, В.О. (Physico-technological Institute of Metals and Alloys, 2024)
Ductile cast irons with a pearlitic metal base are widely used in manufacture of a large range of highly-load machine parts. World leaders in the field of ductile cast iron are successfully manufacturing parts from new grades of pearlitic ductile cast irons, which have a 2-5 times higher minimum relative elongation A, compared to the requirements of current Ukrainian standards. Traditional manufacturing technologies of such cast irons require the use of expensive alloying elements (like nickel and/or copper) in the charge and mandatory energy-intensive heat treatment. The article provides comparative data on the effect of modifying with two types of magnesium-containing master alloys (named ferrosilicon-magnesium-calcium FeSi45Mg7Ca4 and nickel-magnesium NiMg15), on the ductile cast irons structure formation and mechanical properties in the as-cast state and after normalizing heat treatment. The obtained results indicate that usage of developed process of original melt modifying and refining with ferrosilicon-magnesium-calcium master alloy FeSi45Mg7Ca4 instead of modifying with nickel-magnesium master alloy NiMg15 and ferrosilicon FeSi75 is a promising and effective way of pearlitic ductile cast iron with increased technological and mechanical properties production at lower energy consumption for castings heat treatment. The developed technology of pearlitic ductile cast iron with Cu = 0.85-1.15 %wt. obtaining via modifying with ferrosilicon-magnesium-calcium master alloy allows to obtain parts with high mechanical properties: tensile strength Rm = 920-952 MPa, relative elongation A = 6,0-8.0 % and 60 % higher cyclic strength compared to nickel-magnesium master alloy using. This shows the possibility to increase the mechanical properties and cyclic durability in parts significantly without introducing of expensive nickel into the ductile cast iron composition. Usage of the melt modifying process with ferrosilicon-magnesium-calcium master alloy instead of modifying with nickel-magnesium master alloy and ferrosilicon doesn’t increase the level of defects in castings and doesn’t create its specific types.